Infants, animals, and the origins of number. (2017) - Margolis, Eric
Abstract: Where do human numerical abilities come from? Leibovich et al. argue against nativist views of numerical development noting limitations in newborns' vision and limitations regarding newborns' ability to individuate objects. I argue that these considerations do not undermine competing nativist views and that Leibovich et al.'s model itself presupposes that infant learners have numerical representations.